Mixing Efficiency Study of Nano and Micro Filled PP Systems - Hargitai, H.; Török, D. (Acta Technica Jaurinensis, 2014)
In this paper micron and nano sized fillers were compounded with polypropylene homopolymer. First masterbaches were produced with high filler content than samples were injection molded by different filler loading. The effect of using static mixers with different element number were analyzed on the mechanical properties and filler distribution. Tensile properties of PP–talc, PP-boron nitride and PP-graphene systems were investigated and optical microscopic observations were carried out for mapping the distribution of the fillers in the polymer matrix.